Housing, travel, and energy spatial-temporal simulation of Riyadh: Impacts of the New Murabba Project - Abdel Rahman Muhsen; John Abraham; Geraldine Fuenmayor; Paul McMillan; J. D. Hunt (Journal of Transport and Land Use)
The city of Riyadh in Saudi Arabia envisions rapid growth, from a 2020 population of 7.2 million to one reaching 15 million or more by 2030 (Alhefnawi et al., 2024). A spatial economic and transport model has been developed following well-established approaches to assist in forecasting the expansion of the city, particularly the spatial organization of the population, people's housing, economic activity and employment consumption, and the flows of goods and services on the transportation network. The model, called the Riyadh PECAS model, was used to analyze the housing, travel, energy consumption, and related spatial impacts of a proposed megaproject, the New Murabba, consisting of 104,000 residences, 9,000 hotel rooms, and 4.8 million square meters of other non-residential space, anchored by a 400-meter cube-shaped megastructure with partially open interior space. The model simulates shifts in housing location, housing dwelling type, travel mode choice, travel distance, and energy use (residential and transportation). It predicts some of the details of housing consumption and location choices of Saudis and non-Saudis that provide additional insight. The non-central location of the new development could increase the total quantity of vehicle distance travelled by 6% when compared to a reference simulation where development locations are market-driven. Complementary investment in major public transit infrastructure could lead to a higher mode-split to transit and a corresponding reduction in transportation energy use. Further analysis of the New Murabba and other growth and policy options using the model could help guide Riyadh's growth.